2014
DOI: 10.1186/1471-2393-14-78
|View full text |Cite
|
Sign up to set email alerts
|

Modeling maternal mortality in Bangladesh: the role of misoprostol in postpartum hemorrhage prevention

Abstract: BackgroundBangladesh is one of the few countries that may actually achieve the fifth Millennium Development Goal (MDG) in time, despite skilled birth attendance remaining low. The purpose of this paper is to examine the potential role misoprostol can play in the decline of maternal deaths attributed to postpartum hemorrhage (PPH) in Bangladesh.MethodsUsing data from a misoprostol and blood loss measurement tool feasibility study in Bangladesh, observed cause specific maternal mortality ratios (MMRs) were estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 30 publications
1
30
0
Order By: Relevance
“…The maternal and newborn care received is also related to delivery location (Murthy et al, 2007). In some developing countries, a large proportion of women have non-institutional delivery (Prata et al, 2014). A study from Ethiopia found institutional delivery service utilization was 38.1% (Ababulgu & Bekuma, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The maternal and newborn care received is also related to delivery location (Murthy et al, 2007). In some developing countries, a large proportion of women have non-institutional delivery (Prata et al, 2014). A study from Ethiopia found institutional delivery service utilization was 38.1% (Ababulgu & Bekuma, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…They found a total of 108 lives saved per 100,000 women delivering at home, using misoprostol for PPH prevention, in a setting where there are an estimated 130 PPH-attributable deaths per 100,000 live births. In a more recent modeling study based on Bangladesh data[ 247 ], with current maternal mortality ratio (MMR) (approximately 200/100,000), evidence from the literature on efficacy, and cause-specific mortality in their study population, the authors determined that with “high coverage” of 80%, using misoprostol after home births approximately 13 deaths could be averted per 100,000 live births (i.e. about 6% lower than current mortality).…”
Section: Resultsmentioning
confidence: 99%
“… Conducted phased trial Obstetric Gynecology Society of Bangladesh (OGSB) Published in peer reviewed journals Misoprostol was included in the program of activities for community health workers and family welfare agents Government Departments - DGHS, Drug Administration Provided technical assistance NGOs-BRAC, Pathfinder International, Engender Health, UN Agencies Researcher’s efforts to promote utilization of study findings “We took a temporary permission from the Drug Administration of Bangladesh to conduct the research and subsequently, after we found that it is effective and useful for prevention of PPH and in collaboration with the drug companies and the pharmaceutical licensure of Bangladesh we requested them to extend the registration of the use of misoprostol for the prevention of PPH and we informed them that we will provide all the papers and any technical assistance they need and they did it and now misoprostol is registered in Bangladesh for use of in the prevention of PPH and that’s happened because of our research findings” (KII001) Case study 2. Enactment of the Bangladesh Domestic Relations Bill 2010 Characteristics of the study Factors that could have contributed to research utilization Activities to promote utilization Utilization of research findings Policy contribution Study/Authors/years Study design/ population Main findings Research Process (Problem identification) Stakeholder involvement Communication Process Macro-contextual factors Asling-Monemi K, Tabassum Naved R, Perrsson LA, 2008 [ 31 ] Secondary analysis of longitudinal data from rural Bangladesh of 2691 live-born children in relation to their mother's experience of physical, sexual and emotional partner violence and level of controlling behaviour in marriage. Under five-mortality was 88 per 1000 in this cohort.…”
Section: Resultsmentioning
confidence: 99%